Crystal Structure of a Soluble APOBEC3G Variant Suggests ssDNA to Bind in a Channel that Extends between the Two Domains. Issue 23 (20th November 2020) - Maiti, Atanu; Myint, Wazo; Delviks-Frankenberry, Krista A.; Hou, Shurong; Kanai, Tapan; Balachandran, Vanivilasini; Sierra Rodriguez, Christina; Tripathi, Rashmi; Kurt Yilmaz, Nese; Pathak, Vinay K.; Schiffer, Celia A.; Matsuo, Hiroshi
Graphical abstract: Highlights: Co-crystal structure of a soluble variant of APOBEC3G and di-deoxy-cytidine. A positively charged channel, consisting of NTD loop-1 and CTD loop-3, could be a ssDNA binding pathway. Arginine 24 provides a key interaction with ssDNA that is required for efficient deamination. W211 and D316 have a key role in initiating catalytic binding of the deamination target sequences. Our structure provides new insights in the ssDNA binding mechanism of APOBEC3G. Abstract: APOBEC3G (A3G) is a single-stranded DNA (ssDNA) cytosine deaminase that can restrict HIV-1 infection by mutating the viral genome. A3G consists of a non-catalytic N-terminal domain (NTD) and a catalytic C-terminal domain (CTD) connected by a short linker. While the CTD catalyzes cytosine deamination, the NTD is believed to provide additional affinity for ssDNA. Structures of both A3G domains have been solved individually; however, a full-length A3G structure has been challenging. Recently, crystal structures of full-length rhesus macaque A3G variants were solved which suggested dimerization mechanisms and RNA binding surfaces, whereas the dimerization appeared to compromise catalytic activity. We determined the crystal structure of a soluble variant of human A3G (sA3G) at 2.5 Å and from these data generated a model structure of wild-type A3G. This model demonstrated that the NTD was rotated 90° relative to the CTD along the major axis of the molecule, an orientation that forms a positively charged channel connected to the CTD catalytic site, consisting of NTD loop-1 and CTD loop-3. Structure-based mutations, in vitro deamination and DNA binding assays, and HIV-1 restriction assays identify R24, located in the NTD loop-1, as essential to a critical interaction with ssDNA. Furthermore, sA3G was shown to bind a deoxy-cytidine dinucleotide near the catalytic Zn 2+, yet not in the catalytic position, where the interactions between deoxy-cytidines and CTD loop-1 and loop-7 residues were different from those formed with substrate. These new interactions suggest a mechanism explaining why A3G exhibits a 3′ to 5′ directional preference in processive deamination.